2013
DOI: 10.7205/milmed-d-13-00055
|View full text |Cite
|
Sign up to set email alerts
|

Military Nursing Care of Iraqi Patients

Abstract: The purpose of this phenomenological study was to understand military nurses' experiences of care for Iraqi patients. Analysis yielded three themes-expanding practice, ethical dilemmas, and the cultural divide. "Expanding practice" is the nurses' descriptions of their personal initiative to seek opportunities for learning additional knowledge and skills so that they would be competent to provide care for all ages of patients from newborns to the elderly with a wide variety of complex diagnoses. "Ethical dilemm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 12 publications
3
36
2
Order By: Relevance
“…The optimal status of cultural attitude is congruent with a study from Eche and Aronowitz 17 in which they reported a high average score of cultural desire among cultural care subscales. A study by Goodman and et al 24 in Iraq reported a lack of nurses' cultural awareness, which approves the finding in the present study. Kardong-Edgren et al 25 showed that nurses' cultural attitude and competence were at an average level and their cultural awareness was moderate to high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The optimal status of cultural attitude is congruent with a study from Eche and Aronowitz 17 in which they reported a high average score of cultural desire among cultural care subscales. A study by Goodman and et al 24 in Iraq reported a lack of nurses' cultural awareness, which approves the finding in the present study. Kardong-Edgren et al 25 showed that nurses' cultural attitude and competence were at an average level and their cultural awareness was moderate to high.…”
Section: Discussionsupporting
confidence: 92%
“…As well, the results of a quasi-experimental study conducted by Bunjitpimol et al 26 showed significant differences between the intervention and control groups in terms of cultural knowledge after the intervention and also revealed that continuous training courses are needed for cultural attitude, performance and competence. In the study conducted by Goodman et al to investigate cultural awareness in Iraqi nurses, the results suggested that nurses require training about cultural customs and values of patients 24 ; in the present study, too, nurses' cultural awareness was poor and they require cultural care education. In addition to the status of cultural care dimensions, the present study assessed the correlation between the dimensions of cultural care (preparation, attitude, awareness and competence) which showed a moderate to high correlation between them.…”
Section: Discussioncontrasting
confidence: 44%
“…The key for increasing cultural awareness is to improve the understanding of health inequities and health disparities (Cantey, Randolph, Molloy, & Cary, 2017). It is also crucial that nursing students raise their awareness on the communication and cultural beliefs of people (Goodman, Edge, Agazio, & Prue-Owens, 2015). There are different strategies to promote cultural awareness and competency within nursing programs (Eshleman & Davidhizar, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This case study promoted a great amount of emotion and challenging examples that the team had to navigate in this austere, multicultural environment. Agazio and Goodman [7] and Goodman et al [8] found that during wartime nursing, practice nurses were at a loss at times as to how best to manage key situations and they recommended that more education is needed in ethical decisionmaking before, during, and after deployment as a debriefing strategy. Our team could absolutely agree with this and this is an area that could be isolated for development due to the spontaneity and intensity of the possible scenarios staff can face.…”
Section: Inter-cultural Practice and Educationmentioning
confidence: 99%